EFEKTIVITAS KOMUNIKASI DALAM MENCEGAH FRAUD PADA PENGADAAN BARANG DAN JASA - I Wayan Indra Wiguna Murti; Wayan Ardhi Wirawan; Joko Prayitno (IAHN Gde Pudja Mataram, 2022)
Fraud could happen in all sectors, one is sector procurement of goods and services. Commission eradication Corruption KPK finds almost 80% cases of corruption it handles sourced from deviation in the procurement of goods and services. Lack of communication is one reason from happening this fraud. The study focused on four things, that is, form communication, Obstacles, solutions to resolve Constraints, and implementation of effective communication to prevent fraud in the procurement of goods and services. destination study this that is find and analyze forms, constraints, solutions, and implementation communication to prevent fraud in the procurement of goods and services. Methodology Study use method qualitative descriptive, with type data collection using technique observation, interview, and documentation. Data analyzed through stages reduction, exposure, and withdrawal conclusion so that Becomes results study in the form of suggestions or recommendations. As for results of research, this show, that the shape of communication carried out is communication organization, communication group, and verbal/non-verbal communication conducted in meetings or discussions between work units. Obstacles found that is miscommunication and networking communication. solution resolve constraint that is clear instructions, stop assuming, becomes a good listener, write important information, and submit a question. Implementation of effective communication in the procurement of goods and services at IAHN Gde Pudja Mataram that effective communication one that is respected tall during the procurement process of goods and services. Communication was effective and important for preventing happening cheating and having a great effect big in progress procurement goods and services environment government good center or area.